Age, Parity, Education, and Antenatal Care (ANC) Among Pregnant Mother in Working Area of Citra Medika Public Health Center Lubuklinggau - Yuni Rahmadhaniati; Vina Nopita; Septa Mandala (Jurnal Sains Kesehatan, 2018)
The antenatal care (ANC) is an examination of pregnant women during pregnancy to prevent complications and prepare for healthy births. This study aimed to study the factors related to ANC among  pregnant women in  working area of Citra Medika Public Health Center Lubuklinggau. The type of  this study used was Deskriptif Correlation with Cross Sectional design. The population in this study was all postpartum mothers in working area of Citra Medika Public Health Center Lubuklinggau amounted 151 mothers. Sampling technique was Total Sampling. This study was conducted during month of July-August 2017 at Citra Medika Public Health Center Lubuklinggau. Analysis data in this study used univariate and bivariate analyses with Chi-Square statistical test. The results of the study were: 77 mothers (51.0%) did not complete their ANC visit,  91 mothers (60.3%) were middle education, 78 mothers (51.7%) aged 20-35 years old, 104 mothers (68.9%) with multipara parity. There was a significant correlation between maternal education with ANC visit  with closeness of the relationship was medium category, there was a significant correlation between maternal age with ANC visit with closeness of the relationship was medium category, and there was                 a significant correlation between parity with ANC visit with closeness of                                  the relationship was medium category. Keywords:  age, ANC, education, parity